Economic Tools and Methods for the Analysis of Global Change Impacts on Agriculture and Food Security (Springer International Publishing, 2018)
This book compiles examples of the most widely used tools in agricultural economics that have been developed and used to analyze the impact of global change in agricultural activity. The research papers on this topic are plenty but lack the methodology. The content of this book can be used by research students exploring additional methods in agricultural economics.